Avaliação espectrofotométrica in vitro da influência do gel clareador e de protocolos de irradiação sobre a cor dental - Ferreira, Ana Carolina de Oliveira (2012)
The current literature is not sufficiently complete as to clarify whether there are better associations of gel and protocol to the tooth whitening, because of the existence of large amounts of gels, light sources and irradiation protocols available for the treatment. Thus, this study aimed to: a) verify whether the protocols of irradiation tested for each light source are able to raise the whitening potential of each gel; b) verify whether there is a better whitening gel for each protocol of irradiation. Bovine tooth specimens were randomly allocated to nine treatments (n=14), which included three gels: Lase Peroxide Sensy (LPS), White Gold Office (WGO) and Placebo (PL), two light sources: Whitening Lase Light Plus (WLLP) Thera Lase Surgery (TLS) and the absence of irradiation as a control. The color of the specimens was measured by an intraoral spectrophotometer, VITA Easyshade Compact, according to the CIE L*a*b* system, in two experimental times: before and after seven days of the treatments. From the L*, a* and b* color coordinates, the values of the changes ∆L*, ∆a*, ∆b*, ∆C* and ∆E* were calculated. ∆E* was used to determine whether there was variation in color of the specimens after the treatments. The variables ∆L*, ∆a*, ∆b* and ∆C* were used to investigate how the change in color was obtained. The placebo gel promoted the same values of ∆E*, with or without light sources, always below the visually perceptible. The LPS and WGO bleaching gels promoted ∆E* values greater than those generated by the placebo gel (p<0.05), always above the considered visually perceptible. To the LPS gel, ∆E* values promoted with bleaching were the same regardless of the use of light sources. To the WGO gel, the achieved values of ∆E* with WLLP light source was superior to that obtained with the TLS light source (p<0.001) and without irradiation (p<0.001). For the WLLP light source, it was not found significant difference between the ∆E* values obtained with the LPS and WGO gels. For the TLS light source, the obtained ∆E* value with the LPS gel was greater than with the WGO gel (p<0.001). Without irradiation, the ∆E* value promoted by LPS gel was higher than that achieved with the WGO gel (p=0.002). The ∆L* and ∆b* values were the determinants of color variations obtained after the treatments (p<0,001). It was concluded that no protocol of irradiation was able to increase the capacity of the whitening gel LPS. The WGO gel had its effectiveness increased when the WLLP protocol of the irradiation was used. With the WLLP protocol irradiation, the two bleaching gels obtained the same bleaching ability. According to the protocol of irradiation of the TLS light source and without the use of irradiation, LPS gel had better bleaching results than the WGO gel.